Dimensi Kinerja Dosen Dalam Meningkatkan Prestasi Mahasiswa - Riska Affriani (Management of Education: Jurnal Manajemen Pendidikan Islam, 2024)
In an effort to make the nation's life more intelligent, increasing the quality of teachers is considered very important because quality teachers are expected to produce students who are qualified, agile, moral and useful for the nation. The aim of this research is to analyze the implementation of academic supervision in an effort to improve the quality of the nation. This research was designed using qualitative methods with a case study approach. Data collection was carried out using interview observation and documentation techniques. The analysis procedure goes through the stages of data collection, data reduction, data presentation, and drawing conclusions, while data testing in this study uses triangulation. Based on the research that has been carried out, it can be seen that in implementing supervision activities, it must go through at least 3 (three) stages, namely: planning, implementation and evaluation. In planning actions, the school principal will issue a letter containing the decisions and schedule for carrying out the supervision. Then, in the implementation of the supervision activity, it is carried out by monitoring the teacher's performance in the classroom and after completion, it is entered into an evaluation activity where the school principal will assess and provide solutions if there are problems.